Education for sustainability: A new challenge for the current university model (Research, Society and Development, 2018)
Education for Sustainable Development aims to disseminate and promote a set of principles and values within the university model through management, teaching, research and university extension. It does not focus on a specific area but covers many areas such as equality, peace, health, sustainable urbanization, the environment. The objective of this study is to make an appeal in all these areas so that universities incorporate the dimension of sustainability in their curricula, through teaching, research and university management. For this, the different international and regional initiatives that have emphasized the need for Universities to be committed to the culture of sustainability and their inclusion in the current university model have been analyzed. The work will conclude with the idea that a sustainable development is perhaps one of the key pieces in the conception of the University of the 21st century.